Simplified Rapid Protocol for Assessing the Thoracic Aortic Dimensions and Pathology with Noncontrast MR Angiography - Verma, Megha; Yarlagadda, Bharath; Hendrani, Aditya; Bhat, Ambarish P.; Kumar, Senthil (International Journal of Angiology, 2019)
Contrast enhanced magnetic resonance angiography (CE-MRA) is limited by long acquisition time and contrast exposure in aortic emergencies. To compare the effcacy of dark blood (DB) and bright blood (BB) noncontrast sequences with the gold standard CE-MRA using a novel protocol for performing consistent thoracic aortic measurements and thoracic aortic pathologies identifications. A total of 66 patients with suspected or known thoracic aortic pathology who underwent CE-MRA underwent DB and BB imaging prior to CE-MRA for planning purposes. Aortic dimension was measured at 10 standard reference points in the ascending, arch, and descending aorta. Detection of aortic pathologies was recorded individually for each noncontrast sequence. When comparing the CE-MRA to the DB images and CE-MRA to the BB images, a majority of the measurement differences were less than or equal to 2 mm or resulted in no change of diagnostic class (95% for CE-MRA vs. DB and 96% for CE-MRA vs. BB). Of the patients who had major changes in diagnostic class (e.g., changes in two or three classes), the absolute measurements were not clinically significant in any given patient to warrant a change in management. Individually, the DB and BB sequences allowed for accurate recognition of all 47 aortic pathologies. DB and BB sequences produced comparable and consistent measurements of the thoracic aorta when compared with CE-MRA. In a situation where CE-MRA is not readily available or contraindicated, noncontrast MRA using our protocol is a reliable alternative to CE-MRA for assessment of aortic pathologies.
Keywords: noncontrast magnetic resonance angiography; dark blood; bright blood; thoracic aortic pathologies; thoracic aortic measurements; contrast-enhanced magnetic resonance angiography; thoracic aortic assessments